2020
DOI: 10.1161/circ.142.suppl_3.16798
|View full text |Cite
|
Sign up to set email alerts
|

Abstract 16798: Evidence of Abnormal T1 Mapping in Arrhythmic Mitral Valve Prolapse Without Significant Mitral Regurgitation

Abstract: Background: Prior cardiac magnetic resonance (CMR) studies have reported abnormal T1 mapping, reflective of diffuse myocardial fibrosis, in patients with mitral valve prolapse (MVP) and ventricular arrhythmias. However, T1 mapping was derived from conventional Look-Locker sequences and/or obtained in selected MVP patients with severe mitral regurgitation (MR) and a clinical indication for CMR. Hypothesis: We hypothesize that extracellular volume (ECV) f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…The native (without contrast) T1 values increase, while interstitial fibrosis increases; post-contrast T1 values become shorter, and their combination in a formula that also uses the patient’s hematocrit allows for calculation of the ECV [ 63 ]. Various studies have suggested that both native T1 values and ECVs are increased in MR patients and have demonstrated significant prognostic value [ 51 , 64 , 65 , 66 ]. In addition to that, feature tracking involves retrospective processing of common SSFP images which tracks myocardium in a way that is similar to speckle tracking in advanced echocardiography [ 67 ].…”
Section: Application Of Cmr In Primary and Secondary Mitral Regurgita...mentioning
confidence: 99%
“…The native (without contrast) T1 values increase, while interstitial fibrosis increases; post-contrast T1 values become shorter, and their combination in a formula that also uses the patient’s hematocrit allows for calculation of the ECV [ 63 ]. Various studies have suggested that both native T1 values and ECVs are increased in MR patients and have demonstrated significant prognostic value [ 51 , 64 , 65 , 66 ]. In addition to that, feature tracking involves retrospective processing of common SSFP images which tracks myocardium in a way that is similar to speckle tracking in advanced echocardiography [ 67 ].…”
Section: Application Of Cmr In Primary and Secondary Mitral Regurgita...mentioning
confidence: 99%